Integrated care for geriatric frailty and sarcopenia: a randomized control trial. Issue 1 (26th August 2016) - Chan, Ding‐Cheng (Derrick); Tsou, Hsiao‐Hui; Chang, Chirn‐Bin; Yang, Rong‐Sen; Tsauo, Jau‐Yih; Chen, Ching‐Yu; Hsiao, Chin‐Fu; Hsu, Ya‐Ting; Chen, Chia‐Hui; Chang, Shu‐Fang; Hsiung, Chao Agnes; Kuo, Ken N.
Abstract: Background: Exercise, nutrition, and psychological interventions may all have positive impacts on frailty and sarcopenia. However, it is not known whether an integrated care programme with all three components can be beneficial and the intensity of such programme is also not certain. In this study, we aim to determine the effectiveness of two levels of integrated care on frailty and sarcopenia. Methods: A randomized control trial was conducted at two community hospitals in Taiwan. Older adults (65–79 years of age, N = 289) who scored ≥1 on the Cardiovascular Health Study Phenotypic Classification of Frailty (CHS_PCF) were enrolled in the trial. Low‐level care (LLC) participants received a 2 h education course on frailty, sarcopenia, coping strategy, nutrition, and demonstration of study exercise programme. Educational multimedia material was distributed as reference for home practice with bi‐monthly telephone follow‐ups on adherences. High‐level care (HLC) participants, in addition to LLC instructions, received six sessions of on‐site problem solving therapy and 48 exercise sessions within 6 months. Brief nutrition consultation was also provided during the exercise sessions. Primary outcome was improvement of the CHS_PCF by at least one category (from pre‐frail to robust, or from frail to pre‐frail or robust) from baseline. Secondary outcomes included changes of individual frailty, and sarcopenia indicators. Assessments were done at 3, 6, and 12 months by trained research assistants blinded to randomization status. Intention‐to‐treat analysis was applied. Results: Mean age was 71.6 ± 4.3 years, with 53% females. For the entire cohort, improvement of primary outcome was 35% at 3 months, increased to 40% at 6 months, and remained stable at 39% at 12 months. Improvement rates were similar in both groups. Compared with the LLC group, HLC participants had greater improvements in the following indices: energy expenditure of walking, 5 m walking time, dominant hand grip strength, timed‐up‐and‐go‐test, and one‐leg‐stand time — mainly at 6 and 12 month assessments. Conclusions: The 6 month integrated care improved frailty and sarcopenia status among community‐dwelling elders, with high‐intensity training yielding greater improvements. Low‐level care could be promoted as a basic intervention, while HLC could be reserved for those at high risk and with high motivation.